ENHANCING HEALTH SERVICES IN THE MANAGEMENT OF TUBERCULOSIS (TB) AT THE CLASS III YOUTH CORRECTIONAL INSTITUTION OF LANGKAT - Christo Zhedilo L Sembiring; Vivi Sylviani Biafri (Universitas Nusa Cendana, 2026)
This study explores efforts to improve tuberculosis (TB) health services at the Class III Youth Correctional Institution in Langkat, Indonesia, using the Donabedian Model, which examines structure, process, and outcome aspects of healthcare delivery. The research highlights that TB remains a serious issue in correctional settings due to overcrowding, poor sanitation, and limited medical resources, requiring more systematic and integrated health service improvements. Using a qualitative approach, the findings reveal that the quality of TB services is still constrained by inadequate facilities, limited healthcare personnel, and inconsistent screening and documentation practices, which lead to delays in diagnosis and treatment. To address these challenges, the study proposes the SIPETIK (Integrated Clinical Tuberculosis Screening System) program, which focuses on improving digital medical records, implementing routine screening, strengthening health education, and enhancing collaboration with external health institutions. In conclusion, improving TB control in correctional facilities requires strengthening infrastructure, increasing staff competence, and integrating policies more effectively. The SIPETIK program offers a strategic and replicable model to enhance prison healthcare systems while supporting broader public health goals, particularly in the effort to eliminate tuberculosis. Keywords: Tuberculosis (TB); Prison Health; Donabedian Model; Healthcare Quality; SIPETIK Program